PROSPECTIVITY OF FINALIZATION IN SERHIY ZHADAN’S NOVEL "THE ORPHANAGE" - Feliks Shteinbuk (Езиков свят)
The article is devoted to Serhiy Zhadan’s novel "The Orphanage", which is considered by modern criticism mainly from a socio-political and ethical perspective because of the theme of war as the final crisis of a long complex history. The purpose of the research is to propose an interpretation of Zhadan’s novel The Orphanage based on the principles of hermeneutic and comparative-typological methods, as well as applying elements of narrative analysis taking into account the artistic potential of a finalization phenomenon. As a result, the prospective nature of finalization is justified and the appropriate typology of this poetic phenomenon is singled out. According to the actual version, the typology consists of four types, namely, extra plot-spatial, oneiric-imaginary, eidetic, and narrative ones. These types correlate with each other, hence, a whole poetic block emerges, which actualizes the new meanings presented in the work, and deepens the content of the novel’s loci communes. In particular, the listing of three days in the titles of the novel’s chapters indicates a real continuation of the list. Moreover, the title of the novel against such a background expresses its ontological content, which is additionally underscored by oneiric-imaginary pictures and the eidetic way of representing these images; instead, the diegetic shift due to the change of narrators returns the novel narrative from the level of ontological-existential symbolism to the level of personal formation of the novel subject.